PERANAN TRICHODERMA HARZIANUM TERHADAP PERKEMBANGAN JAMUR AKAR PUTIH PADA BIBIT KARET - , SURATUL IKHLAS K, Prof. Dr. Ir. Bambang Hadisutrisno, DAA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Hevea is one of the important commodities in Indonesia, because other than as the source of state revenue is also a livelihood for more than 12 million residents, as well as commodities that can assist the development of remote areas. White root disease caused by the Rigidoporus microporus is kind of a disease that are harmful for hevea plantation. aims this study is to determine inhibition of Trichoderma harzianum against the white root and the use of T. harzianum in suppressing the emergence of white root disease in the nurseries. The research conducted in laboratory of Agricultural Micology with testing the antagonistic nature of T. harzianum and mikoparsitisme test against the R. microporus. Results of laboratory studies showed that the diameter of the fungus R. microporus on day 7 without fungus T. harzianum greater 2.91 cm compared in diameter R. microporus with fungus T. harzianum 2.70 cm by percentage inhibition 7.21%. On the of test mikoparasitisme hifa of T. harzianum wrapped around hifa R. microporus so the growth is hampered. The research results of screen house obtained percentage who of symptomatic plants due to disease attack of white root in consist of : P01: 0.00%, P02: 16,68 %, P1: 17,34 %, P2: 18,72 %, P3: 10,70 %, P4: 5,71 % with the average of 11,52 %. Smallest percentage of obtained are of treatment P01 (water): 0.00%, and the largest of obtained on treatment P2 (5 g T. harzianum / polibag) : 18,72 %, while the intensity of the white root disease at each treatment P01: 0.00%, P02: 0,53 %, P1: 0,59 %, P2: 0,62 %, P3: 0,46 %, P4: 0,26 % with the average of 0,41 %. Smallest percentage of obtained are of treatment P01 (water): 0.00%, and the largest of obtained on treatment P2 (10 g T. harzianum / polibag) : 1,78%. Mechanisms controllingT. harzianum against R. microporus form of competition in the use of nutrition and mycoparasitism.Hevea is one of the important commodities in Indonesia, because other than as the source of state revenue is also a livelihood for more than 12 million residents, as well as commodities that can assist the development of remote areas. White root disease caused by the Rigidoporus microporus is kind of a disease that are harmful for hevea plantation. aims this study is to determine inhibition of Trichoderma harzianum against the white root and the use of T. harzianum in suppressing the emergence of white root disease in the nurseries. The research conducted in laboratory of Agricultural Micology with testing the antagonistic nature of T. harzianum and mikoparsitisme test against the R. microporus. Results of laboratory studies showed that the diameter of the fungus R. microporus on day 7 without fungus T. harzianum greater 2.91 cm compared in diameter R. microporus with fungus T. harzianum 2.70 cm by percentage inhibition 7.21%. On the of test mikoparasitisme hifa of T. harzianum wrapped around hifa R. microporus so the growth is hampered. The research results of screen house obtained percentage who of symptomatic plants due to disease attack of white root in consist of : P01: 0.00%, P02: 16,68 %, P1: 17,34 %, P2: 18,72 %, P3: 10,70 %, P4: 5,71 % with the average of 11,52 %. Smallest percentage of obtained are of treatment P01 (water): 0.00%, and the largest of obtained on treatment P2 (5 g T. harzianum / polibag) : 18,72 %, while the intensity of the white root disease at each treatment P01: 0.00%, P02: 0,53 %, P1: 0,59 %, P2: 0,62 %, P3: 0,46 %, P4: 0,26 % with the average of 0,41 %. Smallest percentage of obtained are of treatment P01 (water): 0.00%, and the largest of obtained on treatment P2 (10 g T. harzianum / polibag) : 1,78%. Mechanisms controllingT. harzianum against R. microporus form of competition in the use of nutrition and mycoparasitism.